Biotargets for mediation of arsenic–induced coronary heart disease by calycosin. Issue 1 (31st December 2022) - Xu, Hongyuan; Qin, Lixiu; Nie, Litao; Li, Lin; Guo, Peng; Chen, Yizhao; Huang, Chuang; Su, Min; Yang, Bin
ABSTRACT: Arsenic (As), an environmental pollutant, is a highly poisonous metalloid. Accumulated evidence has shown the association between As exposure and elevated risk of the development of coronary heart disease (CHD). Calycosin, a beneficial flavonoid, has demonstrated cardioprotective activities, including those against CHD, in preclinical studies. The anti-As-related CHD activity and mechanism of calycosin have not yet been elucidated. Here, we aimed to determine the core biotargets and molecular mechanisms of calycosin against As-interrelated CHD via integrated bioinformatic analysis, including network pharmacology and molecular docking. The network pharmacology data demonstrated 41 intersection genes of calycosin against As-related CHD, prior to the identification of 15 core targets. Additional in silico investigation indicated that mitogen-activated protein kinase-3 (MAPK3), epidermal growth factor receptor (EGFR), and interleukin-6 (IL6) were the primary pharmacological targets of calycosin for the treatment of As-related CHD. In addition, the therapeutic effects can be realized via cardioprotection-associated signaling pathways for reducing As-induced myocardial toxicity and impairment and boosting CHD functional reparation. In summary, calycosin mediates potent pharmacological effects in As-related CHD therapy functioning via multiple targets and multiple pathways. The results may eventually aid in promoting future clinical application after experimental verification.